2020
DOI: 10.1177/1744806920926426
|View full text |Cite|
|
Sign up to set email alerts
|

CXCL12/CXCR4 signaling induced itch and pain sensation in a murine model of allergic contact dermatitis

Abstract: Allergic contact dermatitis is a skin inflammatory disease manifested with itch and pain symptom around the inflamed area. Chemokines such as CXCL12 are involved in the pathophysiology of allergic contact dermatitis, but little has been known about the effect of CXCL12/CXCR4 signaling for nociceptive sensation accompanying allergic contact dermatitis. Our study showed that CXCL12 and CXCR4 were upregulated in trigeminal ganglion with the progression of allergic contact dermatitis through western blotting and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Helfrich et al found an 8-fold increase in CXCR4 expression in lesional skin from ETR patients compared to HC 51 . Su et al demonstrated that in the mouse model of allergic contact dermatitis, the CXCL12/CXCR4 signaling pathway induces itching and pain feeling 52 . It requires further study to determine whether the CXCL12/CXCR4 signaling pathway has a role in some rosacea and acne patients with itching and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Helfrich et al found an 8-fold increase in CXCR4 expression in lesional skin from ETR patients compared to HC 51 . Su et al demonstrated that in the mouse model of allergic contact dermatitis, the CXCL12/CXCR4 signaling pathway induces itching and pain feeling 52 . It requires further study to determine whether the CXCL12/CXCR4 signaling pathway has a role in some rosacea and acne patients with itching and pain.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 activates TG by binding to CXCR4, thereby exacerbating pain and itching caused by inflammation. 143 Collectively, numerous reports have shown that CXCR4 antagonists can be used to improve and prevent skin inflammation. A natural fragment of serum albumin, named EPI-X4, has also been found to improve dermatitis.…”
Section: Allergic Contact Dermatitis (Acd)mentioning
confidence: 99%
“…TG contains a large number of pain afferent nerves, where neurons overexpress CXCR4 under ACD conditions. CXCL12 activates TG by binding to CXCR4, thereby exacerbating pain and itching caused by inflammation 143 …”
Section: Cxcr4/cxcl12 Axis–mediated Inflammatory Diseasesmentioning
confidence: 99%
“…Intradermal injection of CXCL12 (1 mg/10 mL) enhanced the itch-scratching behavior, which was relieved by CXCR4 antagonism (AMD3100, 5 mg/kg). 164 The CXCL10/ CXCR3 axis contributes on a spinal cord level to chronic itch in mouse models of dry skin and allergic contact dermatitis. [165][166][167] Another chemokine, CCL2, can directly activate CCR2-expressing cutaneous small-diameter DRG neurons, resulting in itch-and pain-like behaviors.…”
Section: Role Of Chemokines For Pruritus In Admentioning
confidence: 99%